Viola de dez cordas: entre a tradição e a contemporaneidade - Renato Teixeira Almeida (2013)
The primary aim of this research was, try to understand, based on a critical analisys of the ten strings viola, how and where was made the caipira tradition of this instrument. For which meanings and re-meanings it passed until it gain the nickname viola caipira and how are the index and icons that compose this caipira tradition of the viola, so musical so extra-musical. Furthermore, we also try to understand how this tradition is figure out and how it is presented nowadays. After that, the next aim was discuss how the notions of tradition and contemporarity act on ten strings viola in relationship with its execution, reception, learning or transmition in a way to trans-form, or not, its image that is, until that, intimately connected with the country world. Furthermore, was try to evaluate if, and in how level, this new scene, which seems full of dualisms, in one moment, antagonistic in other, complementary, influence and built the viola players performance in different generations, nowadays. To achieve this objectives, were made questionaries with some people which were related with the world of ten string viola, professionals, amateurs or its admirers. For a better construction of our argument, were also made interviews with some of the most important names of actual imagem of ten strings viola. These datas were confronted among them, with the literature and with the opinion of the author of this paper, which is a viola player too.